2018
DOI: 10.1038/s41598-018-31386-6
|View full text |Cite
|
Sign up to set email alerts
|

Microparticles from β-thalassaemia/HbE patients induce endothelial cell dysfunction

Abstract: Thromboembolic complication occurs frequently in β-thalassaemia/HbE patients, particularly in splenectomised patients. Endothelial cells play an important role in thrombosis. There is strong evidence of endothelial cell activation and dysfunction in β-thalassaemia. Microparticles (MPs) are associated with thrombosis and endothelial cell dysfunction in many diseases including β-thalassaemia. However, the effect of thalassaemic-MPs on endothelial cells mediating thrombus formation has not been elucidated. In thi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

5
32
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
9
1

Relationship

1
9

Authors

Journals

citations
Cited by 29 publications
(37 citation statements)
references
References 31 publications
5
32
0
Order By: Relevance
“…Moreover CD11b level, which is a marker of monocytic activation, was significantly lower in patients than controls (P=0.004), these results were in agreement with both. Kheansaard et al, who have studied the origin and the effect of circulating microparticles in thalassemic and reported that the increased microparticles in thalassemia are not monocytic derived and confirmed that other types of MPs play an important role on thrombosis and vascular dysfunction in β-thalassaemia, 18 and Elsayeh et al, who reported an increase in the total MPs in thalassemic patients who had previous history of thrombosis or pulmonary hypertension, however monocytic microparticles did not increase. 19 This finding was explained by Slater et al, who reported that iron overload in thalassemic patients can modulate monocytic functions and activation through inhibition of TLR4 (toll-like receptor 4) which is responsible for monocytes activation by TLR4 -endothelial signaling.…”
Section: Discussionmentioning
confidence: 87%
“…Moreover CD11b level, which is a marker of monocytic activation, was significantly lower in patients than controls (P=0.004), these results were in agreement with both. Kheansaard et al, who have studied the origin and the effect of circulating microparticles in thalassemic and reported that the increased microparticles in thalassemia are not monocytic derived and confirmed that other types of MPs play an important role on thrombosis and vascular dysfunction in β-thalassaemia, 18 and Elsayeh et al, who reported an increase in the total MPs in thalassemic patients who had previous history of thrombosis or pulmonary hypertension, however monocytic microparticles did not increase. 19 This finding was explained by Slater et al, who reported that iron overload in thalassemic patients can modulate monocytic functions and activation through inhibition of TLR4 (toll-like receptor 4) which is responsible for monocytes activation by TLR4 -endothelial signaling.…”
Section: Discussionmentioning
confidence: 87%
“…BT intermedia and major forms are both associated with a hypercoagulable state and increased incidence of thrombosis [ 157 , 158 ]. Elevated levels of circulating EVs including RBCEVs in BT are reported in multiple studies [ 159 , 160 , 161 , 162 , 163 , 164 , 165 ]. In splenectomized BT patients, a significant increase in the number of circulating RBCEVs is observed compared to non-splenectomized patients [ 159 , 160 , 164 , 165 ].…”
Section: Biological Roles Of Rbcevsmentioning
confidence: 99%
“…Higher apoptotic rate and caspase 3/7 activity and reduced viability were observed in endothelial, liver, and pancreatic cells after stimulation with βT vs. control EVs. Previously, Kheansaard and his colleagues demonstrated that microparticles from individuals with βT/HbE induce EC dysfunction [ 32 ]. Our group previously demonstrated that monocyte-derived EVs induce apoptosis in ECs [ 33 ].…”
Section: Discussionmentioning
confidence: 99%